(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Viktoria A. Beresneva (Kirov, Russian Federation) The article presents categorical description of the phenomenon of language syncretism, called by the author as linguistic syncretism on the material of time forms in the German language for the first time in linguistics. Application of the famous epistemological admission to the interpretation of linguistic facts allowed to implement the linguistic syncretism in the general theory of the unity of the world and describe it as a phenomenon if integrative linguathinking human activity. The term «linguistic syncretism», based on the close connection between being and knowledge, is interpreted by the author in two ways: as a syncretism of language forms and a linguistic interpretation of the phenomenon of syncretism. Interpretation of linguistic syncretism as a dual linguistic category led ultimately to the characterization of linguistic syncretism as the embodiment and reflection of the world unity. It is given the methodology and the main results of the categorical analysis of the problem of linguistic syncretism. Due to the categorical scientific and linguistic research syncretism involving data philosophy and psychology about the patterns of being and thinking was able to recreate a complete picture of the ontological and logical syncretism as well as the mechanism of linguistic syncretism, reveal the inner logic of formation and development of the phenomenon of syncretism. The study contributes to the development of the theory of syncretism, as well as specified in the title of the article as general linguistic ideas in the direction of the in-depth study and understanding of the relationship and interaction of elements of the system and the results of their interaction. Key words: linguistic syncretism, evolution, system, structure, unity of the world